THE PREVALENCE OF ARTERIAL HYPERTENSION AND THE SPECIFIC FEATURES OF DEVELOPMENT OF LEFT VENTRICULAR HYPERTROPHY IN RADIATION-EXPOSED PERSONS - S. K. Kukushkin; E. A. Martynchik; E. M. Manoshkina; A. Yu. Kharitonov; V. M. Shamarin (Klinicist, 2015)
Moscow Aim – to study the prevalence of arterial hypertension (AH) and left ventricular hypertrophy among male liquidators (ML) of Chernobyl accident consequences and a group of unorganized males (UM) from one of the Moscow regions. Materials and methods. The results of examining a random representative sample of three hundred and ninety-five 35–64-year-old Mos-cow Registry MLs of Chernobyl accident consequences (n = 395; 79 % response rate) were analyzed. A random sample of males from one of the Moscow regions (n = 382; 70 % response rate) was used to make up an age-matched comparison group.Results. The age-adjusted prevalence rate (AAPR) of AH according to the expanded WHO criteria (> 140/90 Hg mm) was substantially higher among MLs than among UMs (64.9 and 54.7 %, respectively; p < 0.01). The prevalence of AH was associated with the men’s age in both populations. Thus, this among MLs and UMs in the 35–44 year age group was 54.6 and 47.2 %, respectively and in the 55–64 year age group 80 and 62.2 % (i.e. the incidence of AH increased by 1.3 (р < 0.01) and 1.2 (р < 0.05) times, respectively). Conclusion. AAPR of AH among the liquidators was significantly higher than that in the control group (64.9 % versus 54.7 %, respectively). In the compared groups, that of left ventricular hypertrophy did not differ and was 25 and 25.6 %, respectively; significant differences were found in the degree of left ventricular hypertrophy: certain (concentric) left ventricular hypertrophy was more common in the liquidators than in the comparison group (12.9 % versus 7.4 %, respectively). In the ML group compared to the control group, there was much higher awareness of having AH (59.1 % versus 46 %, respectively), drug treatment was performed in 38.7 % versus 7.9 %; effective BP control in the patients was 13.1 % versus 4.7 %, respectively.